2004
DOI: 10.1021/ma048199d
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and Molecular Weight Control of the Polymerization of Acrylamide via RAFT

Abstract: The reversible addition−fragmentation chain transfer (RAFT) polymerization of acrylamide (AM) was studied in order to establish reaction conditions which would provide optimal rates of monomer conversion and to determine reasons for deviation of theoretical and experimental molecular weights, the former predicted from current models. To this end, chain transfer agents (CTAs) and initiators were selected and experiments performed in water and in dimethyl sulfoxide (DMSO) at specified CTA/initiator ratios and te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
176
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(193 citation statements)
references
References 43 publications
(108 reference statements)
14
176
0
1
Order By: Relevance
“…S, [44,53] AA, [13,14] MA, [14,64,77,81] BA-b-AA, [14,77] MA-b-EA [14,77] BA, [9,14,44,77] (MMA), [44] S [9,82] 22 [9] S, [6,9,13,14,44,53,55] MA, [44,81,83,84] S-AN, [13,14] S-MMA, [14] MMA-HEMA, [13,14] BA, [9,14] MMA, [13,14,44,52,77] BzMA, [77] MMA-BA, [5] HEMA-iBMA-MMA-S, [14] DMAEMA, [6] XMA, [65,66] AM, [73] MMA-b-MAA, [14,77] MMA-...…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…S, [44,53] AA, [13,14] MA, [14,64,77,81] BA-b-AA, [14,77] MA-b-EA [14,77] BA, [9,14,44,77] (MMA), [44] S [9,82] 22 [9] S, [6,9,13,14,44,53,55] MA, [44,81,83,84] S-AN, [13,14] S-MMA, [14] MMA-HEMA, [13,14] BA, [9,14] MMA, [13,14,44,52,77] BzMA, [77] MMA-BA, [5] HEMA-iBMA-MMA-S, [14] DMAEMA, [6] XMA, [65,66] AM, [73] MMA-b-MAA, [14,77] MMA-...…”
mentioning
confidence: 99%
“…S, [14,46,96] AA, [63,97] MA [96] S-MAH [98] S 55 S 96 - [99] AA, [99] HEA, [99] EA, [99] AA-b-EA, S-b-AA, BA, [99,100] (MMA), [99] AM [73] EHA-b-EA [99] NC 58 [46] H 3 C-S---S, [6,46,96] MA, [6,96] MMA [6,96] - [15,101] BA [101] -…”
mentioning
confidence: 99%
“…The deviation from pseudo first order kinetics at higher conversion was accompanied with a decreased polymerization rate already at medium conversions where RAFT agent hydrolysis and aminolysis influenced the polymerization process [67]. Albertin et al also observed the RAFT agent hydrolysis in the RAFT polymerization of methacrylic glycomonomer in the presence of added base.…”
Section: Controlled Radical Miniemulsion Polymerizationmentioning
confidence: 97%
“…Also, by varying the amount of RAFT agent used, the length of the resulting polymers can be controlled 18 . However, the molar ratio of the RAFT agent to initiator should always be greater than two to assure the low dispersity of the product.…”
Section: Binding Tests Of the Synthetic Glycopolymers With Lectin-coamentioning
confidence: 99%